2021
DOI: 10.7759/cureus.15662
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor as a Clinical Biomarker in Predicting the Development of Post-Stroke Depression: A Review of Evidence

Abstract: Studying the relationship between brain-derived neurotrophic factor (BDNF) and post-stroke depression (PSD) may help determine the potential for depression in stroke patients at the earliest stage possible. Current research has identified changes in BDNF levels in PSD patients. Thus, this article was intended as a review of evidence with respect to changes in the expression of BDNF in patients with PSD by integrating extant findings. We conducted a search in the electronic databases PubMed, EMBASE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…It binds to tyrosine kinase receptor B (TrkB) and plays a crucial neurotrophic role [58][59][60][61]. Its functions include nourishing damaged neurons, regulating neural plasticity, depicting a vital role in the survival, differentiation, growth, and postinjury repair of neurons, and participating in the initiation and development of depression, regarded as a landmark indicator for the diagnosis of depression [62,63]. Many studies have revealed that the expression of BDNF and its high-affinity receptor TrkB protein in the thalamus decrease after PSD, indicating PSD occurrence is tightly associated with BDNF level, and the lesser the production of BDNF, the more likely PSD will occur [64,65].…”
mentioning
confidence: 99%
“…It binds to tyrosine kinase receptor B (TrkB) and plays a crucial neurotrophic role [58][59][60][61]. Its functions include nourishing damaged neurons, regulating neural plasticity, depicting a vital role in the survival, differentiation, growth, and postinjury repair of neurons, and participating in the initiation and development of depression, regarded as a landmark indicator for the diagnosis of depression [62,63]. Many studies have revealed that the expression of BDNF and its high-affinity receptor TrkB protein in the thalamus decrease after PSD, indicating PSD occurrence is tightly associated with BDNF level, and the lesser the production of BDNF, the more likely PSD will occur [64,65].…”
mentioning
confidence: 99%
“…The association between neurotransmitters and PSD has not yet been clearly demonstrated. The results of previous studies on the association between a reduction in BDNF and PSD development are contradictory [16]. Among seven studies investigating the association between BDNF and the pathogenesis of PSD, five confirmed a significant association between them, but two studies could not.…”
Section: Discussionmentioning
confidence: 81%
“…Among seven studies investigating the association between BDNF and the pathogenesis of PSD, five confirmed a significant association between them, but two studies could not. Additionally, even the five studies that confirmed the association observed the association only in the early stage of stroke in most cases [16]. From the psychological and social perspectives, depression occurs due to physical discomfort and maladaptation to it [17,18], and the patient's sex is also associated with the development of PSD [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF and cortisol are believed to be biomarkers of MDD [ 34 , 62 ], in particular, serum cortisol and mature BDNF are among the specific biomarkers with a potential on the evaluation of MDD chronicity [ 63 ]. Current research has identified associations between changes in serum BDNF levels and post-stroke depression [ 64 ]. In our study, serum BDNF was reduces in both groups with epilepsy, PWE, and PWCED; in the PWMDD group, the decrease showed a statistically significant trend, the mean value being similar to that of two groups with epilepsy.…”
Section: Discussionmentioning
confidence: 99%